Orman alanlarının turizm yatırımlarına tahsisi konusunda turizmi teşvik kanunu'nda öngörülen değişiklikler - ÜSTÜN, GÜL (My University, 2021)
İklim krizi kaynaklı ısınmalar sebebiyle Türkiye’nin de yer aldığı Akdeniz iklim kuşağı bölgesi devasa orman yangınlarına şahitlik etmektedir. Orman yangınlarının devam ettiği tarihlerde ise 7334 sayılı Kanun ile Turizmi Teşvik Kanunu’nda değişiklik yapılmıştır. Bu çalışmada orman yangınlarının aktüelliği ışığında dikkat çekilen bu değişiklik irdelenecektir. Anayasa Mahkemesi’ne konu olan söz konusu düzenlemelerin iklim krizinin hem nedeni hem de sonucu olarak önemli rol oynayan orman alanlarının korunması ve geliştirilmesi konusunda korumaya ağırlık veren bir koruma-kullanım dengesi çerçevesinde değerlendirilmesi gerektiği düşünülmektedir.

The Mediterranean Climate Zone, including Turkey has witnessed many massive bushfires to which climate change-driven warming has led. The Law No. 7334 which amends the provisions of the Law for the Encouragement of Tourism entered into force in bushfires days. Taking advantage of the recency of forest fires, this study explores the up-front amendments. The legislation is now under the review of the Constitutional Court. It is considered that the Court should evaluate these provisions in the light of sustainable development principles which enables to balance the protection of environment, social and economic use of public property
The amendments of the law for the encouragement of tourism regarding the allocation of forest to tourism investments
Keywords: Forest; Bushfire; Tourism; The Law No.7334; Tourism Centre; Orman; Orman Yangını; Turizm; 7334 Sayılı Kanun; Turizm Merkezi